Spectroscopy of the CO-H2 van der Waals molecule - Salazar, Mary; Paz, José; Hernández, Antonio (Ciencia, 1970)
In the present contribution, we have reviewed he spectroscopic techniques generally used to collect intermolecular interaction data on van der Waals molecules, with special emphasis on the experimental and theoretical background of the spectroscopy of CO-H2. This analysis showed that the potential energy surface of CO-H2 had to be recalculated by using free-parameter fully ab initio calculations with basis sets of proven quality. Our fully ab initio calculations within the supermolecule approach for the potential energy surface of the diatomic van der Waals CO-H2 showed that the linear O-C”¦H-H structure corresponds to the most stable conformation in the ground CO(X1Î£+)-H2(X1Î£g) electronic configuration. The calculated dissociation energy corresponded to a D0 of 4.9meV with at least one vibrational state supported by this linear configuration, which agrees well with existing spectroscopic results.